ANALISIS KONSEP TEO-FILOSOFIS TAUHID DAN DVAITA VEDANTA (STUDI KOMPARATIF) - Ni Luh Komang Indah Sari; Pande Wayan Renawati; I Gusti Putu Gede Widiana (Widya Sandhi Jurnal Kajian Agama Sosial dan Budaya, 2022)
This research focuses on the study of theo-philosophical concepts in Tauhid and Dvaita Vedanta. Both concepts view God as causa prima and different from the human spirit and material nature. Through interpretive and hermeneutic frameworks of thought, in the study of religions, it is certainly very interesting to explore the theological teachings in it. This is even more so in terms of the theo-philosophical concepts of Tauhid and Dvaita Vedanta. In fact, Tauhid and Dvaita Vedanta both view God as personal, having character, and different from humans. Both also position God who has a distance from humans. Furthermore, the aspect of difference is rooted in an epistemological framework, namely Tauhid bases his aqidah on the commands and words of Allah, while Dvaita Vedanta does not base bhakti on God's commands, but through Lela and Krida as the basis. Therefore, Dvaita Vedanta views love as the basis for connecting with God (bhakti yoga). Understanding the two concepts of Tauhid and Dvaita Vedanta will create a unifying reflection in terms of similarities and differences.